Seasonal Variations in Nutritional Profile of Notopterus notopterus: Implications for Consumer Choice, Aquaculture Diversification, and Food Security - Debnath, Chandan (Fishery Technology, 2025)
This study investigated seasonal variations in thenutritional composition of Notopterus notopterus, apotential species for aquaculture diversification inIndia. Samples were collected across four seasons in Tripura, India, and analyzed for proximate composition and mineral content. Significant seasonal variations were observed in protein, lipid, ash, moisture content, and mineral composition (p